Promiscuous gating modifiers target the voltage sensor of Kv7.2, TRPV1, and Hv1 cation channels. Issue 6 (5th March 2014) - Kornilov, Polina; Peretz, Asher; Lee, Yoonji; Son, Karam; Lee, Jin Hee; Refaeli, Bosmat; Roz, Netta; Rehavi, Moshe; Choi, Sun; Attali, Bernard
ABSTRACT: Some of the fascinating features of voltage‐sensing domains (VSDs) in voltage‐gated cation channels (VGCCs) are their modular nature and adaptability. Here we examined the VSD sensitivity of different VGCCs to 2 structurally related nontoxin gating modifiers, NH17 and NH29, which stabilize Kv 7.2 potassium channels in the closed and open states, respectively. The effects of NH17 and NH29 were examined in Chinese hamster ovary cells transfected with transient receptor potential vanilloid 1 (TRPV1) or Kv 7.2 channels, as well as in dorsal root ganglia neurons, using the whole‐cell patch‐clamp technique. NH17 and NH29 exert opposite effects on TRPV1 channels, operating, respectively, as an activator and a blocker of TRPV1 currents (EC50 and IC50 values ranging from 4 to 40 μM). Combined mutagenesis, electrophysiology, structural homology modeling, molecular docking, and molecular dynamics simulation indicate that both compounds target the VSDs of TRPV1 channels, which, like vanilloids, are involved in π‐π stacking, H‐bonding, and hydrophobic interactions. Reflecting their promiscuity, the drugs also affect the lone VSD proton channel mV‐SOP. Thus, the same gating modifier can promiscuously interact with different VGCCs, and subtle differences at the VSD‐ligand interface will dictate whether the gating modifier stabilizes channels in either the closed or the open state.—Kornilov, P., Peretz, A., Lee, Y., Son, K., Lee, J. H., Refaeli, B., Roz, N., Rehavi, M., Choi, S., Attali, B. Promiscuous gating modifiers target the voltage sensor of Kv 7.2, TRPV1, and Hv 1 cation channels. FASEB J . 28, 2591–2602 (2014). www.fasebj.org